2021
DOI: 10.1007/s12015-021-10162-6
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Potential of DPSCs and Revascularization: Direct, Paracrine or Autocrine Effect?

Abstract: A new source of mesenchymal stem cells has recently been discovered, the so-called dental pulp derived stem cells (DPSCs) which therefore could represent potentially tools for regenerative medicine. DPSC originate from the neural crest and are physiologically involved in dentin homeostasis; moreover, they contribute to bone remodeling and differentiation into several tissues including cartilage, bone, adipose and nervous tissues. DPSCs have also been shown to influence the angiogenesis process, for example thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 104 publications
(139 reference statements)
0
42
0
Order By: Relevance
“…Several recent reviews have documented the current knowledge and understanding of DPSCs’ differentiation into vital lineages including their angiogenic and neurogenic potential ( Ratajczak et al, 2016 ; Mortada et al, 2018 ; Mattei et al, 2021 ), odontogenic and chondrogenic potential ( Nuti et al, 2016 ; Ching et al, 2017 ; Mortada and Mortada, 2018 ), and periodontal and dental tissue regeneration ( Hu et al, 2018 ; Zhai et al, 2019 ); Therefore, we will focus in this section in summarizing the current knowledge regarding DPSCs hepatogenic and pancreatic β-cells differentiation capacities.…”
Section: Dental Pulp Stem Cells Potential Role In Tissue Repair and Flourishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reviews have documented the current knowledge and understanding of DPSCs’ differentiation into vital lineages including their angiogenic and neurogenic potential ( Ratajczak et al, 2016 ; Mortada et al, 2018 ; Mattei et al, 2021 ), odontogenic and chondrogenic potential ( Nuti et al, 2016 ; Ching et al, 2017 ; Mortada and Mortada, 2018 ), and periodontal and dental tissue regeneration ( Hu et al, 2018 ; Zhai et al, 2019 ); Therefore, we will focus in this section in summarizing the current knowledge regarding DPSCs hepatogenic and pancreatic β-cells differentiation capacities.…”
Section: Dental Pulp Stem Cells Potential Role In Tissue Repair and Flourishmentmentioning
confidence: 99%
“…Taken together, DPSCs secretome and exosome are rich in trophic factors that can mediate tissue regeneration and proliferation, which could be highly useful for prospective cell-free regenerative medicine and advantageous over interventions involving cell transplantation ( Vizoso et al, 2017 ). Nevertheless, a proper characterization of the DPSCs’ secretome and exosome is required since they are significantly influenced by culture conditions ( Chin et al, 2021 ), hypoxia ( Aranha et al, 2010 ), insult ( Mattei et al, 2021 ), DPSCs passage ( Faruqu et al, 2020 ), subpopulation ( Nakashima et al, 2009 ), and stage of differentiation ( Huang et al, 2016 ).…”
Section: Paracrine Activity Of Dental Pulp Stem Cells: Secretome and Exosomesmentioning
confidence: 99%
“…This is because preconditioning with melatonin not only maintains the self-renewal characteristics and promotes osteogenic differentiation of DPSCs but also plays a powerful redox regulator and a cellular protective role in preventing cellular damage from local in ammation, oxidative stress, and hypoxic environments [26,31,67] . However, the activated DPSCs contribute to bone healing via direct cell-to-cell interaction/communication or by indirect factor secretion, including cytokines, growth factors, extracellular vesicles, and exosomes within the defect area, which trigger the regulatory signals and provide a complex microenvironment or niche for mediating tissue regeneration [9,68] . These results demonstrated that melatonin-preconditioning DPSCs loaded in MBCP bone-grafting materials can e ciently enhance bone regeneration and bone remodeling turnover in calvarial defects.…”
Section: Discussionmentioning
confidence: 99%
“…Among various MSC sources, dental pulp-derived MSCs (DPSCs) have been used in tissue engineering and regenerative medicine due to their easy isolation and minimally invasive harvesting from discarded premolars or third molars [4][5][6]. DPSCs have strong odontogenic, osteogenic, and angiogenic potential [7][8][9] . Compared with bone marrow-derived MSCs (BMSCs), DPSCs can survive in vitro for a longer time; exhibit a higher growth rate; and produce more extracellular matrix, mineralized tissue, and bone-like trabecular structures with less immunosuppressive properties [7,[10][11][12][13].…”
mentioning
confidence: 99%
“…The plasticity and differentiation potential of these cells has been demonstrated using differentiation techniques [5,[26][27][28][29][30][31] and also their high proliferation capability when compared to chondrocytes [32][33][34]. Dental pulp stem cells (DPSCs) have become one of the most common stem cells used in several studies [25,35 ] , because of their easy accessibility, plasticity, high proliferative ability, and their multiple differentiation capability (chondrogenic, odontogenic, and neurogenic, among others) compared with other MSCs from bone marrow or adipose tissue origin [36][37][38]. The use of DPSCs in cartilage tissue repair has been reported by several authors (for a review, see [39]).…”
Section: Introductionmentioning
confidence: 99%